2015
DOI: 10.1016/j.comptc.2014.09.007
|View full text |Cite|
|
Sign up to set email alerts
|

More insight in multiple bonding with valence bond theory

Abstract: An original procedure is proposed, based on valence bond theory, to calculate accurate dissociation energies for multiply bonded molecules, while always dealing with extremely compact wave functions involving three valence bond structures at most. The procedure consists of dividing the bond-breaking into sequential steps, thus breaking one by one the separate components of the multiple bond. By using the Breathing-Orbital Valence Bond method (P.C. Hiberty, S. Shaik, Theor.Chem. Acc. 108 (2002) 255-272), it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Very recently, a theoretical study by Hendrick et al. appeared where the nature of the bonding in N 2 , C 2 and CO was analyzed with VB methods . The authors introduced a stepwise procedure for breaking the triple bond in N 2 and the alleged quadruple bond in C 2 , which gives numerical values for each in‐situ bond.…”
Section: Resultssupporting
confidence: 85%
“…Very recently, a theoretical study by Hendrick et al. appeared where the nature of the bonding in N 2 , C 2 and CO was analyzed with VB methods . The authors introduced a stepwise procedure for breaking the triple bond in N 2 and the alleged quadruple bond in C 2 , which gives numerical values for each in‐situ bond.…”
Section: Resultssupporting
confidence: 85%
“…In two-electron bonds, it is the interference between ( ↑ − ↓ ) and ( ↓ − ↑ ) states built from fragment-localized orbitals (in a valence-bond picture) which gives rise to covalent stabilization. Multiple bonds have access to even more states (within a few kcal/mol of the ground state) 45 . It is important to note that for charge-shift bonds like in F 2 , significant stabilization is also gained by the relaxation of the requirement of fragment locality, which results in a wavefunction (in a generalized valence-bond picture) in which both ionic and covalent structures are present.…”
Section: Discussionmentioning
confidence: 99%
“…The ELF basins have indeed a quite different physical meaning [37], and may or may not match the chemists' expectation of visualizing a volume that could be associated to the space-localization of the bonding electron pair(s). In the case of N 2 , in a paper to be found in this same special issue [38], one of us has indeed shown that the p bonds in dinitrogen have substantially charge-shift character. It is known that charge-shift bonds lead to very small disynaptic basins, if any, and that a substantial part of the bonding density is found in these cases in the monosynaptic basins associated to the lone pairs [39].…”
Section: Covalent Bondingmentioning
confidence: 91%